Odyssey Classic : Ginger Pye - Eleanor Estes (U.S.A Harcourt Brace Jovanovich, 1951)
When the Pye family's puppy, Ginger, disappears on Thanksgiving Day, the children are convinced that he has been adbucted by a stranger in a yellow hat.
Keywords: Fiction + Newbery Award Book -- Fiction + Newbery Award Book